Experience of Management of Stricture Oesophagus - KHAN, A Z; NAQI, S A; ABID, K J; AHMAD, N; A SHAFI, S T (Annals of King Edward Medical University, 2017)
A two and a half year study from January 2000 to June 2002 regarding the management of oesophageal stricture was carried out at West Surgical Ward of Mayo Hospital, Lahore and Surgical Unit-I of Sir Ganga Ram Hospital, Lahore. The study comprised of 20 patients. All the patients underwent exploratory laparotomy. Forty five percent of the patients were male. 35-40% of the total patients were in the age group between 16-3lyears.Seventy five percent of our patients underwent transhiatal oesophagectomy and in 20% feeding gastrostomy was done as the malignancy was advanced and inoperable. Majority of our patients were followed up for 6 months to one year. There was no per operative and immediate postoperative mortality in our study. Twenty percent of our patients who had inoperable malignant stricture died within a few months of their exploration. Our series showed that transhiatal oesophagectomy produced good results in terms of safety and oncological adequacy in moderately advanced tumours and benign lesions. It also holds promise of lesser complications.